2016
DOI: 10.31599/jkn.v2i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Ahmadiyah dan Hak atas Kebebasan Beragama di Indonesia

Abstract: Kasus Jemaat Ahmadiyah Indonesia adalah fenomena kekerasan berbasis agama dan kebebasan beragama yang menarik perhatian publik. Di samping kasusnya sangat banyak, pengikut organisasi ini berjumlah lebih dari 300.000 orang di seluruh pelosok tanah air, juga mengundang pro-kontra yang berkepanjangan. Penelitian ini ingin mengetahui lebih jauh tentang isu hak-hak sipil kelompok minoritas, terutama hak kebebasan beragama yang menjadi komponen penting dalam prinsip Hak Asasi Manusia. Penulis berkesimpulan bahwa ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…JA. 5/23/13 (March 13, 1953), which confirmed that JAI was protected by law (Ahmadiyah.id, 2022), (2) NU, Indonesia's largest Islamic organization, which protects their human rights (Ahmad, 2010), and (3) Legal and humanitarian institutions that defend their religious beliefs and rights (Ummah, 2016;Yosarie et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…JA. 5/23/13 (March 13, 1953), which confirmed that JAI was protected by law (Ahmadiyah.id, 2022), (2) NU, Indonesia's largest Islamic organization, which protects their human rights (Ahmad, 2010), and (3) Legal and humanitarian institutions that defend their religious beliefs and rights (Ummah, 2016;Yosarie et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Eksistensi kelompok Ahmadiyah hingga saat ini masih menjadi persoalan. Sejak kedatangan Ahmadiyah ke Indonesia pada 1924, kehadirannya menuai banyak kontroversi, terutama terkait konsep nubuwat (kenabian) yang mereka yakini (Ummah, 2016).…”
Section: Pendahuluanunclassified
“…The researches in Ahmadiyah sect tend to fall into two categories: Firstly, the Ahmadiyah sect as a spiritual-theological religious movement has formed the paradigm of the caliphate, which came to the conclusion that the title of the caliph comes from Allah with a mandate to unite the people of the world (Fadli 2007;Muhtador 2016). Secondly, the Ahmadiyah sect has been considered as a heretical sect, an infidel, an enemy of Islam and a traitor of Islam, such that the Ahmadiyah sect has often attracted threats and acts of abuse or violation (As'ad 2009; Irawan 2017; Noor, Syamsiyatun & Banawiratma 2013;Ummah 2016).…”
Section: Introductionmentioning
confidence: 99%